The role of digital human resources management in achieving administrative creativity: An exploratory study of the opinions of a number of managers and department heads in a number of private companies in the city of Dohuk. (Entrepreneurship Journal for Finance and Business, 2025)
The current research aims to determine the role of digital human resources management in achieving administrative creativity, a survey study of the opinions of a number of administrative staff in a number of colleges and institutes at Duhok Technical University in order to test the research hypotheses therein. As for the nature of the data collection method, the questionnaire was relied upon as a primary tool for collecting data by distributing forms to a sample of administrative staff in the researched sample, as (49) forms were distributed, and (45) of them were valid for analysis, which was done using the (SPSS) program. The research produced a set of conclusions, the most important of which is the existence of a significant correlation between digital human resources management and administrative creativity, and the existence of a significant impact of digital human resources management in achieving administrative creativity in the researched colleges. The research presented a set of proposals, the most important of which is enhancing awareness within the researched colleges and at all administrative levels of the importance of moving towards applying digital human resources management by holding training courses for its importance in bringing about changes in the performance of these departments in order to achieve administrative creativity in them.